Epsomite as flame retardant treatment for wood: Preliminary study. (15th November 2016) - Elvira-León, J.C.; Chimenos, J.M.; Isábal, C.; Monton, J.; Formosa, J.; Haurie, L.
Graphical abstract: Highlights: Epsomite as flame retardant for wood has been investigated. Epsomite is highly soluble in water at room temperature (731 g L −1 ). A high concentration solution of Epsomite can be used to impregnate wood. Epsomite decomposes endothermically in a wide range of temperatures. Epsomite acts as a heat sink lowering the temperature and delaying the ignition. Abstract: The effect of epsomite as flame retardant for wood has been investigated and compared with a commercial boron salt. Both flame retardants have been introduced into wood samples by vacuum impregnation. Epsomite is a hydrated sulphate salt with a water solubility of 731 g L −1 at room temperature. Thanks to this high solubility it was possible to obtain elevated epsomite loadings in comparison with the borax salt. Flame retardancy was evaluated by means of the limiting oxygen index, the dripping test and the exposition to a direct flame (Bunsen test). The results showed that the addition of epsomite increases the limiting oxygen index, delays the time to ignition and the evolution of the temperatures trough the wood.